COVID-19 reduces cardiorespiratory fitness even months after a mild to moderate acute phase: a retrospective cohort study - Štěpánek, Ladislav; Nakládalová, Marie; Sovová, Eliška; Štěpánek, Lubomír; Boriková, Alena; Sovová, Markéta; Moravcová, Katarína; Ožana, Jaromír; Jelínek, Libor (Infectious diseases, 2023)
BACKGROUND: COVID-19 survivors may experience long-term health problems, including deterioration of cardiorespiratory fitness (CRF), as demonstrated by several cross-sectional studies that compared the results of cardiopulmonary exercise tests (CPET) performed only after COVID-19 with predicted values. This study aimed to analyze a change in CRF between repeated CPETs in response to suffered COVID-19. METHODS: A total of 127 healthcare workers (HCWs; mean age 55.7 years) underwent two CPETs with a mean interval of 762 days. Forty HCWs suffered from COVID-19 (mild to moderate severity) in the interim (321 days before the second CPET), and 87 HCWs formed a control group. Mixed-effects regression with multiple adjustment and interaction terms was used for two response variables - maximum oxygen uptake (VO2 max) and power output. RESULTS: Between both CPETs, mean VO2 max decreased statistically significantly in the COVID-19 subgroup (by 3.12 mL/kg/min, p = .034) and insignificantly in controls (by 0.56 mL/kg/min, p = .412). The proportion of HCWs achieving predicted VO2 max decreased from 75.9% to 59.5% (p = .161) in COVID-19 survivors, while it increased from 73.8% to 81% (p = .274) in controls. COVID-19 (β = -0.66, p = .014) and body mass index (β = -0.49, p < .001) were independent negative predictors of VO2 max change. COVID-19 was not associated with a change in power output. CONCLUSIONS: On the basis of repeated CPETs, COVID-19 significantly, albeit rather modestly, reduces CRF almost one year after infection. The reduction persists even after the acute phase with mild or moderate severity.
Keywords: Retrospective Studies; průřezové studie; spotřeba kyslíku; Oxygen; retrospektivní studie; kyslík; lidé středního věku; kardiorespirační zdatnost; COVID-19; Cardiorespiratory Fitness; Middle Aged; Humans; lidé; Cross-Sectional Studies; Oxygen Consumption